A Business Architecture Framework for Streamlining Post-Production Workflows in the Film Industry - Wilson; Alfa Ryano Yohannis; Erick Dazki (TEPIAN, 2025)
The post-production phase of filmmaking is a complex sequence of activities that directly impacts artistic quality, cost-efficiency, and time-to-market. Despite advancements in editing suites and asset repositories, many studios face fragmented systems, manual bottlenecks, and version-control conflicts. This paper presents a comprehensive Business Architecture framework, modeled using ArchiMate and aligned with the TOGAF Architecture Development Method (ADM), to transform post-production into an integrated, transparent ecosystem. We systematically map the current ("as-is") and envisioned ("to-be") states across business, application, and technology layers to identify critical inefficiencies, such as redundancy in asset handling and gaps in process standardization. Key recommendations, derived directly from this architectural analysis, include deploying a cloud-based Digital Asset Management (DAM) solution, instituting standardized handoff and approval workflows, and embedding granular metadata strategies to enhance searchability. These targeted interventions not only streamline collaboration and minimize manual rework but also accelerate overall delivery timelines. By systematically applying a robust enterprise architecture framework to a creative industry often characterized by ad-hoc solutions, this research provides a practical blueprint for studios to achieve sustained operational excellence and strategic agility.